The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/htj.21635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of using plastic nanofuel as a fuel in a light‐duty diesel engine

Abstract: A novel nanofuel is formulated using aluminum oxide (alumina) nanoparticles (AONs) in neat plastic oil (PO). A light-duty compression-ignition engine is used in the present investigation to analyze the effect of a 100% plastic nanofuel under different concentrations of nanoparticle on performance, combustion, and emission characteristics. The modified fuels used for conducting the experiment were formulated by mixing PO with 100, 150, and 200 mg/L of AON. The results of the physical and chemical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In a similar approach, nanofuels containing Al 2 O 3 nanoparticles in pyrolysis oil were combusted in a lightduty compression-ignition engine at different concentrations of nanoparticles (100−200 ppm). 295 At 200 ppm nanoparticle concentration, lower in-cylinder pressure, delay period, and combustion duration were observed compared to neat pyrolysis oil. Thermal efficiency was comparable and gaseous emissions were reduced, which was even lower than diesel.…”
Section: Applications Of Pyrolysis Productsmentioning
confidence: 94%
See 1 more Smart Citation
“…In a similar approach, nanofuels containing Al 2 O 3 nanoparticles in pyrolysis oil were combusted in a lightduty compression-ignition engine at different concentrations of nanoparticles (100−200 ppm). 295 At 200 ppm nanoparticle concentration, lower in-cylinder pressure, delay period, and combustion duration were observed compared to neat pyrolysis oil. Thermal efficiency was comparable and gaseous emissions were reduced, which was even lower than diesel.…”
Section: Applications Of Pyrolysis Productsmentioning
confidence: 94%
“…In this case, BTE increased by 2.1% for the pyrolysis oil compared to neat pyrolysis oil with a considerable drop in CO, hydrocarbon, and smoke emissions. In a similar approach, nanofuels containing Al 2 O 3 nanoparticles in pyrolysis oil were combusted in a light-duty compression-ignition engine at different concentrations of nanoparticles (100–200 ppm) . At 200 ppm nanoparticle concentration, lower in-cylinder pressure, delay period, and combustion duration were observed compared to neat pyrolysis oil.…”
Section: Applications Of Pyrolysis Productsmentioning
confidence: 99%
“…This mixture represents an interesting alternative to standard fuel. In study [24], the authors examined the performance of a CI engine using fuel derived from plastic with the addition of aluminum oxide nanoparticles in proportions of 100, 150, and 200 mg/L. The analysis showed that the addition of aluminum oxide shortens the autoignition delay period.…”
Section: Introductionmentioning
confidence: 99%